Complementary distribution patterns of arthropod detritivores (woodlice and millipedes) along forest edge‐to‐interior gradients. Issue 5 (1st July 2016) - De Smedt, Pallieter; Wuyts, Karen; Baeten, Lander; De Schrijver, An; Proesmans, Willem; De Frenne, Pieter; Ampoorter, Evy; Remy, Elyn; Gijbels, Merlijn; Hermy, Martin; Bonte, Dries; Verheyen, Kris
Abstract: Worldwide, forest fragmentation induces edge effects, thereby strongly altering the forest microclimate and abiotic characteristics in the forest edge compared to the forest interior. The impact of edge‐to‐interior gradients on abiotic parameters has been extensively studied, but we lack insights on how biodiversity, and soil communities in particular, are structured along these gradients. Woodlice ( Isopoda ) and millipedes ( Diplopoda ) are dominant macro‐detritivores in temperate forests with acidic sandy soils. We investigated the distribution of these macro‐detritivores along forest edge‐to‐interior gradients in six different forest stands with sandy soils in northern Belgium. Woodlouse abundance decreased exponentially with distance from the forest edge, whereas millipede abundance did not begin to decrease until 7 m inside the forest stands. Overall, these patterns were highly species specific and could be linked to the species' desiccation tolerance. Whereas the observed abundance patterns were independent from forest stand and dominant tree species, tree species had a large effect on community structure. Edge gradients in macro‐detritivores may consequently have implications for nutrient cycling, especially in smaller forest fragments with a large edge‐to‐interior ratio.